Water Security in the Middle East Essays in Scientific and Social Cooperation - Axelrad Cahan, Jean (Anthem Water Diplomacy Series, 2017)
Water Security in the Middle East argues that, while conflicts over transboundary water systems in the Middle East do occur, they tend not to be violent nor are they the primary cause of a war in this region. The contributors in this collection of essays place water disputes in larger political, historical and scientific contexts and discuss how the humanities and social sciences contribute towards this understanding. The authors contend that international sharing of scientific and technological advances can significantly increase access to water and improve water quality. While scientific advances can and should increase adaptability to changing environmental conditions, especially climate change, national institutional reform and the strengthening of joint commissions are vital. The contributors indicate ways in which cooperation can move from simple coordination to sophisticated, adaptive and equitable modes of water management.